Free school meals as an approach to reduce health inequalities among 10-12- year-old Norwegian children - Frøydis N. Vik; Wendy Van Lippevelde; Nina C. Øverby (BMC, 2019)
Abstract Background Children spend a considerable amount of time at school and consume at least one meal/day. This study aimed to investigate if a free, healthy school meal every day for one school year was associated with children's intake of healthy foods at school, weight status and moderating effects of socio-economic status. Methods A non-randomized study design with an intervention and a control group was used to measure change in children's dietary habits at lunchtime. In total, 164 children participated; 55 in the intervention group and 109 in the control group (baseline). Intervention-children were served a free, healthy school meal every school day for one year. Participating children completed a food frequency questionnaire at baseline, at five months follow-up and after one year. Children's anthropometrics were measured at all three timepoints. Intervention effects on children's Healthy food score, BMI z-scores, and waist circumference were examined by conducting a Repeated Measures Multivariate ANOVA. Moderating effects of children's gender and parental socio-economic status were investigated for each outcome. Results A significant intervention effect on children's outcomes (multivariate) between baseline and after one year (F = 2.409, p < 0.001), and between follow-up 1 at five months and after one year (F = 8.209, p < 0.001) compared to the control group was found. The Univariate analyses showed a greater increase in the Healthy food score of the intervention group between baseline and follow-up 1 (F = 4.184, p = 0.043) and follow-up 2 (F = 10.941, p = 0.001) compared to the control group. The intervention-children had a significant increase in BMI z-scores between baseline and follow-up 2 (F = 10.007, p = 0,002) and between follow-up 1 and 2 (F = 22.245, p < 0.001) compared to a decrease in the control-children. The intervention-children with lower socio-economic status had a significantly higher increase in Healthy food score between baseline and follow-up 2 than the control-children with lower socio-economic status (difference of 2.8 versus 0.94), but not among children with higher socio-economic status. Conclusions Serving a free school meal for one year increased children's intake of healthy foods, especially among children with lower socio-economic status. This study may contribute to promoting healthy eating and suggests a way forward to reduce health inequalities among school children. Trial registration ISRCTN61703361. Date of registration: December 3rd, 2018. Retrospectively registered.